The Transformation of Local Culture-Based Character Education in the Society 5.0 Era in Strengthening the Nationalism of the Young Generation - Teuku Muhammad Husni; Sanusi Sanusi; Saiful Saiful; Rizal Fahmi (Jurnal Ragam Pengabdian, 2026)
The Society 5.0 era has brought significant transformations in social life through the integration of digital technology and human-centric innovation, affecting the mindset, behavior, and identity of the younger generation. Amid globalization and digitalization, challenges such as moral degradation, erosion of local cultural values, and weakening of nationalism have become critical educational issues. This study aims to analyze the transformation of local culture-based character education in the Society 5.0 era to strengthen youth nationalism. Using a mixed method approach, this study combines quantitative surveys and qualitative interviews to examine various scientific sources, educational policies, and socio-cultural phenomena in the digital era. The findings reveal that local culture-based character education plays a strategic role in building national identity, strengthening national values, and shaping an adaptive generation without losing cultural roots. The integration of local cultural values through digital media, innovative learning, and digital literacy instills patriotism, tolerance, and social responsibility. A humanistic and local wisdom-based approach is highly relevant in addressing technological disruption challenges. This study concludes that transforming local culture-based character education is a vital strategy to strengthen youth nationalism. Synergy between educational institutions, government, society, and digital technology is essential to create a sustainable character education ecosystem oriented toward strengthening national identity.